Effects of Dad Mardan (Cassia alata) and Ata leaves (Annona reticulata ) against skin diseases of calves (Bangladesh Journal of Livestock Research, 2020)
A number of indigenous plants actively used for therapeutic purpose in Bangladesh. The research work was conducted to investigate the effects of indigenous medicinal plants, Dad Mardan (Cassia alata) and Ata (Annona reticulata) against skin diseases (ringworm, scabies, dermatitis, wounds) in calves. The protective efficacy was observed by the topical application of the 10% combined ointment (Dad Mardan and Ata leaves) and 20% Dad Mardan ointment twice daily on nine calves having skin lesions. Calves treated with combined ointment were almost cured at 21st day of post-treatment whereas calves treated with Dad Mardan ointment were completely healed up after 24th day of post-treatment with the formation of scar tissue and growth of new of hair around the scar tissue and the healing rate was 99.73 % & 99.64 %, respectively. The skin lesions of untreated calves were aggravated with time (5.51% lesion area increased at 24th day from the first inspection). The combined ointment showed the more effectiveness (99.73% healing at 21st days) than the dad mardan ointment (93.76% healing at 21st days) against skin lesions. It may be concluded the ointments of Dad Mardan and Ata leaves can be used as alternative drugs for the treatment of skin diseases in calves.Bangladesh J. of Livestock Res. 20(1-2): 112-118, Jan-Dec 2013